2023
DOI: 10.1002/bdr2.2231
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood location and nutritional resources as a risk factor for congenital heart disease in the fetus

Jennifer Klein,
Julia Ryan,
Pallavi Dwivedi
et al.

Abstract: BackgroundCongenital heart disease (CHD) is the most common birth defect, influenced by maternal health, environmental conditions, and genetics. Maternal health and nutrition, particularly maternal diabetes, is a modifiable risk factor for development of CHD in the fetus. However, the importance of food access during pregnancy on the development of CHD remains unknown. The objective of this study was to investigate the association between maternal neighborhood characteristics, particularly food access, and occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Across socioeconomic lines and divides, for example in urban or rural communities, food deserts exist leading to insufficient nutritional options for mothers, increased rates of obesity, poor diet, and gestational diabetes, among other health issues. Notwithstanding, maternal nutritional choices can be influenced by societal and cultural norms and, again, may be limited by economics and proximity or access to food, as previously stated [6]. As one study demonstrated, these so-called "social-environmental" characteristics that affect nutrition are ".…”
Section: Maternal Health and Associated Factorsmentioning
confidence: 90%
See 2 more Smart Citations
“…Across socioeconomic lines and divides, for example in urban or rural communities, food deserts exist leading to insufficient nutritional options for mothers, increased rates of obesity, poor diet, and gestational diabetes, among other health issues. Notwithstanding, maternal nutritional choices can be influenced by societal and cultural norms and, again, may be limited by economics and proximity or access to food, as previously stated [6]. As one study demonstrated, these so-called "social-environmental" characteristics that affect nutrition are ".…”
Section: Maternal Health and Associated Factorsmentioning
confidence: 90%
“…These disparities start with maternal health and lived experiences that often undermine children with CHDs well before they are born. Extensive literature has documented the impact of maternal health factors, environment, and education on the outcomes associated with CHDs [4][5][6]. These studies have, time and again, highlighted the profound implications these factors have for both the mother and the fetus.…”
Section: Maternal Health and Associated Factorsmentioning
confidence: 99%
See 1 more Smart Citation